Síntese e modificação de nanofios de Bi e Bi2+xTe3-y por implantação e irradiação iônica - Guerra, Danieli Born (2017)
In this work, we investigated the effects of ion implantation and irradiation on the structure and morphology of Bi e Bi2+xTe3-y nanowires exposed to Au and Cu beams with energies ranging from 30 keV to 1 MeV. The wires were grown by template-assisted electrodeposition with diameters of 30, 100 and 130 nm. Bi-rich compounds are obtained at -200 mV using an Ag/AgCl reference electrode. Almost stoichiometric nanowires are obtained at 0 mV vs Ag/AgCl. XRD measurements revealed a polycrystalline structure, with a strong peak in the planes (0 1 5) for Bi-rich wires and a preferential diffraction (1 1 0) for the Te-rich compounds. The dark field TEM analyzes indicates an influence of the nanochannel geometry on the grain size of nanowires. The irradiation parameters were selected based on simulations from SRIM and Iradina programs. The irradiations were performed with the wires deposited in transmission electron microscopy (TEM) grids. The irradiated nanowires presented different morphologies, depending on the irradiation conditions, sometimes presenting a “wavy” morphology. Cu irradiations did not cause significant modifications in the crystalline structure of the samples. For samples irradiated with Au, TEM analysis revealed an amorphized structure, containing an embedded dispersion of small spherical crystallites. Besides, a distribution of nanoparticles dispersed in the vicinity of the irradiated wires was seen on the TEM grids, formed most probably from material redepositing due to sputtering. The 400 keV and 1 MeV Au ions have comparable stopping powers. However, for irradiations at 1 MeV the material underwent a greater erosion process, resulting in the formation of holes through the wires.